Land use change detection along the Pravara River basin in Maharashtra, using remote sensing and GIS techniques - Joshi, Veena; Nagare, Vikas (Acta Geographica Debrecina Landscape & Environment series, 2009)
In the past few decades there has been an increasing pressure of population all over the world, especially in India, resulting in the utilization of every available patch of available land from woodlands to badlands. The study area represents a basin which is economically growing fast by converting the fallow lands, badlands and woodlands to agricultural land for the past few decades. IRS (Indian Remote sensing Satellites) 1 C – LISS III and IRS 1 C PAN and IRS P6 – LISS III and IRS 1 D PAN Images were merged to generate imageries with resolution matching to the landscape processes operating in the area. The images of the year 1997, 2000, 2004 and 2007 were analyzed to detect the changes in the landuse and landcover in the past ten years. The analysis reveals that there has been 20% increase in the agricultural area over the past ten years. Built up area also has increased from 1.35% to 6.36% of the area and dense vegetation also has marginally increased. The remarkable increase in the agricultural area occurs owing to the reclaim of the natural ravines and fallow lands. Presently the area looks promising, but it is necessary to understand the sedimentological and geomorphological characteristics of the area before massive invasion on any such landscapes because the benefit may be short lived.